Kualitas Pelayanan SERVQUAL dan Kepuasan Pasien di Instalasi Gawat Darurat RSUD Siti Fatimah Az-Zahra Sumatera Selatan - Selvi Septiyah Ningsih (MAN 4 Kota Pekanbaru, 2026)
Service quality is a key determinant of patient satisfaction, particularly in Emergency Departments (EDs), where healthcare services must be delivered promptly, accurately, and responsively. This study aims to examine the relationship between SERVQUAL-based service quality and patient satisfaction in the Emergency Department of Siti Fatimah Az-Zahra Regional Hospital, South Sumatra Province. A quantitative approach with a cross-sectional design was employed. Data were collected through questionnaires administered to 94 respondents, consisting of patients and their family members in the ED. Data were analyzed using univariate analysis and the Chi-Square test to examine the relationship between variables. The findings revealed a significant relationship between service quality and patient satisfaction (p < 0.001). These results indicate that better service quality across the SERVQUAL dimensions is associated with higher patient satisfaction in emergency care. This study highlights the importance of improving reliability, responsiveness, assurance, empathy, and tangible aspects of healthcare services to enhance patient satisfaction in hospital emergency departments.